Mixed mucin‐producing and squamous differentiated tumor of the uterine cervix: A report of a case as adenosquamous carcinoma in situ. Issue 1 (7th January 2013) - Ohta, Yoshiki; Kunimura, Toshiaki; Omatsu, Mutsuko; Shiokawa, Akira; Kushima, Miki; Ota, Hidekazu
Abstract We report a non‐invasive mixed mucin‐producing and squamous differentiated tumor of the uterine cervix. This tumor was composed of two cell types: mucin‐producing cells and non‐mucin‐producing cells. These cells were intimately mixed with each other, and showed intraepithelial spreading. The mucin‐producing cells showed signet‐ring or columnar shapes, and were localized to the lower‐to‐upper epithelial layer. The non‐mucin‐producing cells had eosinophilic cytoplasms with a monotonous appearance through the epithelium. Mitosis was sometimes observed in both cell types. Immunohistochemically, both cell types were positive for p16INK4A. The non‐mucin‐producing cells were positive for p63 and 34βE12, suggesting squamous differentiation. Although most mucin‐producing cells were p63‐, a few of them were p63+ and many 34βE12 immunoreactive cells were found in the mucin‐producing cells. This tumor was adenosquamous carcinoma in situ.